(-4+7)-(6+11i)=0

Simple and best practice solution for (-4+7)-(6+11i)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (-4+7)-(6+11i)=0 equation:


Simplifying
(-4 + 7) + -1(6 + 11i) = 0

Combine like terms: -4 + 7 = 3
(3) + -1(6 + 11i) = 0
3 + -1(6 + 11i) = 0
3 + (6 * -1 + 11i * -1) = 0
3 + (-6 + -11i) = 0

Combine like terms: 3 + -6 = -3
-3 + -11i = 0

Solving
-3 + -11i = 0

Solving for variable 'i'.

Move all terms containing i to the left, all other terms to the right.

Add '3' to each side of the equation.
-3 + 3 + -11i = 0 + 3

Combine like terms: -3 + 3 = 0
0 + -11i = 0 + 3
-11i = 0 + 3

Combine like terms: 0 + 3 = 3
-11i = 3

Divide each side by '-11'.
i = -0.2727272727

Simplifying
i = -0.2727272727

See similar equations:

| 2m-5=6m+11 | | 4x=-208 | | .22=logx | | 4x-3=52 | | (3+2i)I=0 | | .22=logs | | (-4+5i)+(3-2i)=0 | | x^2-18y=13 | | 4cos^2x+4sinx-5=0 | | 4y-6+6y+6=90 | | 1.5t=180 | | 15n=-60 | | 42+2y=24 | | 3x-50=x+80 | | x-20=-23 | | 25x+7=17.00 | | 0.5x^2=-2x+3 | | 4x-4=6x-12 | | x-20=-20 | | -3x=-40 | | Y=-11x+9 | | 15y=-3x+9 | | 5(c+2)=30 | | 5(x+12)=140 | | 18=-6k+6+10k | | 1.99(342)=480+x | | (2X+72)-9(X+22)= | | 2b+2+3b=37 | | -6x+-5=1 | | 45m-900=90 | | (20X+21)(3-10X)=0 | | 0.45m-9=9 |

Equations solver categories